Migrant workers in Malaysia: does gain outweigh pain? - Ismail, Fadillah; Md Yusoff, Rosman; Mohammad Shahabuddin, Abu Saim; Nor Aziz, Ainul Mardhiyah (American Scientific Publishers, 2017)
The study is to identify the condition of migrant workers in Malaysia by looking at the case of workers from Bangladesh who migrates to Malaysia in search of employment. One of the primary reasons they want work abroad either temporarily or permanently is because Malaysia has offers a long term benefit for their skills and exposure to a different culture and practices. Their joyful experiences were often unnoticed as it goes hand in hand with the prejudices of their difficult working journey. Their agony of this minority of immigrant apparently caught more attention compared to the pleasure.